(3GdRGgQ aj ZQjH CdaGX eNJUQ GdeRfjs - (3CHj efUhQ eMeO Hf CMeO GdCRgQj GdgQhjs ((3OGQ GdcJGH GdeUQjI s)
(3ChdgG (B:s
(3GdMeO ddg GdgGOj def TGA HaVdI CeG HYO aEfj deG cKQ JUMaj HehGbY BjGJ GdJfRjd heG ChOYfgG Gddg ef GdHjGf GdPj dG jSJZfj Yfg YHGOg s
(3BNQgG (B:s
(3hEdj TQYkG Cj ShGA jbGd GdfGS aj gPG GdCeQ TQY Cj ShGA s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdQGHY YTQs
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjI (B((3dZI (B135) s
Keywords: (3eJaQbGJs